Palaeoproterozoic to Eoarchaean crustal growth in southern Siberia: a Nd-isotope synthesis - Gladkochub, D.; Donskaya, T.; Reddy, Steven; Poller, U.; Bayanova, T.; Mazukabzov, A.; Dril, S.; Todt, W.; Pisarevsky, S. (Geological Society, London, 2009)
Nd-isotope analyses from 114 rock samples are reported from the southern part of the Siberian craton to establish a first-order crustal formation scheme for the region. The Nd-isotopedata show considerable variability within and among different cratonic units. In many cases this variability reflects differing degrees of mixing between juvenile and older (up to Eoarchaean) crustal components. The fragments of Palaeoproterozoic juvenile crust within the studied segment of the Siberian craton margin have Nd-model ages of 2.0-2.3 Ga. Voluminous Palaeoproterozoicgranites ( 1.85 Ga) were intruded into cratonic fragments and suture zones. These granites mark the stabilization of the southern Siberian craton. The complexity in the Nd data indicatea long history of crustal development, extending from the Eoarchaean to the Palaeoproterozoiceras, which is interpreted to reflect the amalgamation of distinct Archaean crustal fragments, with differing histories, during Palaeoproterozoic accretion at 1.9-2.0 Ga and subsequent cratonic stabilization at 1.85 Ga. Such a model temporally coincides with important orogenic events on nearly every continent and suggests that the Siberian craton participated in the formation of a Palaeoproterozoic supercontinent at around 1.9 Ga.